Estudio del impacto de enlaces HVDC sobre la protección de impedancia en el lado AC del sistema (2021)
Due to the occurrence of faults in transmission systems and the sudden changes in voltages and currents caused, it is necessary to establish a protection logic that allows the detection and clearing of faults in an estimated time. Such logic has already developed a theory for HVAC systems. However, the problem lies in the fact that the systems interconnected with HVDC links do not have a sufficient theory or documentation developed on the protections. Therefore, since HVDC systems affect adjacent HVAC systems, it is necessary to document the matter, as it is known that in long distance HVDC links there can be a distortion in the fault current and, therefore, the CTs can saturate and cause delays in the detection time set by the protections. Thus, the objective of this project is to determine the impact on the protections on the AC side of a system interconnected with HVDC links...